Electronic-Based Government System Governance Through Digitalization In The Sabang City Government - Hawary Annisa; Ismail Nurdin; Layla Kurniawati (Sean Institute, 2025)
The implementation of the Electronic-Based Government System (SPBE) in Sabang City faces various obstacles, such as lack of adequate human resources and technology, limited infrastructure, and minimal coordination between agencies. In addition, socialization to the community and the absence of regulations related to data security are also major challenges. This study aims to analyze the governance of SPBE in Sabang City, identify supporting and inhibiting factors for the implementation of SPBE, and formulate efforts to overcome these obstacles in order to support effective and efficient government digitalization. This study uses a descriptive qualitative approach, with data collection techniques through interviews, observations, and documentation studies. Data were analyzed using NVivo software for exploration, coding, and interpretation of results. The study found that SPBE governance in Sabang City is still in the early stages (pilot level) with many indicators not yet met. The main obstacles include limited human resources, lack of government commitment, and geographical challenges. The proposed solutions include strengthening technological infrastructure, increasing digital literacy, developing data security regulations, and optimizing human resources through training and collaboration between parties.